Fail better: response to Holland. Issue 1 (1st January 2019) - Hartwig, Mervyn
ABSTRACT: This is a response to Dominic Holland's critique of Roy Bhaskar's posthumous Enlightened Common Sense, which I edited. Holland claims that his critique is immanent, but I argue that it is not, on two interrelated counts: it fails to achieve hermeneutic adequacy; and criticizes Bhaskar's arguments and positions using mainly transcendent, not immanent, criteria.